Prevention Behavior and Awareness of COVID-19 Pandemic of People in Thai-Myanmar Border Area, Mae Hong Son Province, Thailand - Thongsrikate, Ittipong; Rugchat , Jirawat; Saramad, Pasunit (Asia Social Issues, 2024)
Due to the emergence of the COVID-19 pandemic, affords have been made to block the movement of people and goods. It believed to stop the spread of germs from people and goods in the border area. Nevertheless, the people and goods there do not stand still as specified. This study employed quantitative research to investigate prevention behavior and awareness of the COVID-19 pandemic of people in the Thai-Myanmar border area, Mae Hong Son province, Thailand. A set of questionnaires was used for data collection and administered to a sample group of 406 people living near the border trade relief of Mae Hong Son province. Obtained data were analyzed using descriptive statistics, mean, and standard deviation. Based on behavior and awareness of the prevention of the COVID-19 pandemic, it was found that, as a whole, the respondents had the highest level of COVID-19 prevention behavior (x̅ = 4.24). This included the following instructions for public health personnel: social distancing, wearing a hygienic mask, hand washing, and temperature measurement. For the awareness of the prevention of the COVID-19 pandemic, it was also found at the highest level (x̅ =4.28). This included all people’s participation, communication within the household/community to prevent the COVID-19 pandemic, and strict compliance with the community’s regulations to prevent the disease. The border is a fragile area. There is a chance of transmission of pathogens caused by the movement of people and goods in border areas. The prevention of the COVID-19 pandemic of people in the Thai-Myanmar border area under behavior and awareness of disease prevention. Meanwhile, people worldwide are taking measures to reduce the risk of contracting COVID-19.